(untitled) (Research, Society and Development, 2021)
The objective of this work is to evaluate the effect of foliar application of different doses of silicon on the agronomic performance and occurrence of ’Bordô’ grape downy mildew cultivated in Planalto Norte Catarinense. The experiment was carried out in the 2018/2019 season in a commercial vineyard on a plot of cultivar Bordô, grafted on ‘VR 043-43’, located in the Canoinhas city, Santa Catarina State. The treatments consisted of the following doses of silicon: 0 g L-1 Silicon (control - water application), 150 g L-1 Silicon, 300 g L-1 Silicon and 450 g L-1 Silicon, using the commercial product (Agrisil®, 99% Si). Productive indexes, cluster architecture, technological maturation, disease incidence and severity and disease progress assessment were evaluated. The variables were subjected to analysis of variance (ANOVA) and when treatment effects were detected, the means comparison test was performed using the Tukey Test at 5% probability of error. The foliar application of silicon was efficient for the control of grape downy mildew in the ’Bordô’ variety cultivated in the Planalto Norte Catarinense region, being the dose of 150 g L-1 Silicon more efficient. The foliar application of silicon does not alter the productive indexes, the cluster architecture and the technological maturation of the ’Bordô’ grape, with the exception of the pH variable, which showed an increase in its values with the foliar application of silicon.